2011
DOI: 10.1017/s1068280500008017
|View full text |Cite
|
Sign up to set email alerts
|

Retail Dairy Prices Fluctuate with the Farm Value of Milk

Abstract: Farm milk prices tend to be volatile. Dairy farmers, industry pundits, and policymakers further tend to react to price volatility with alarm. One point of concern is the response of retail prices. This study investigates farm-to-retail price transmission in the 2000s for whole milk and cheddar cheese. Results show that price shocks at the farm gate are transmitted with delay and asymmetry to retail. Differences in the nature of price transmission for whole milk and cheddar cheese prices are also identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…The VECM is designed to deal with prices in related markets that often are cointegrated. Milk‐price transmission studies using VECM frameworks include Capps and Sherwell (), Awokose and Wang (), and Stewart and Blayney ().…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The VECM is designed to deal with prices in related markets that often are cointegrated. Milk‐price transmission studies using VECM frameworks include Capps and Sherwell (), Awokose and Wang (), and Stewart and Blayney ().…”
Section: Previous Studiesmentioning
confidence: 99%
“…The “classic” TVECM continues to be estimated in two steps (e.g., Balke and Fomby, ; Stewart and Blayney, ). In TVECM specifications, the coefficients of the VECM shift depending on the value of the lagged error terms.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Serra and Goodwin (2003) identifi ed asymmetric price relationships for sterilised milk in the Spanish dairy industry, while Lass (2005) found evidence of short-run price asymmetries in the retail milk price in the USA and observed that retail milk prices do not return to the same level following the equivalent price increases and decreases, causing an increase in the marketing margins. Stewart and Blayney (2011) have taken up the debate on asymmetric price transmission by using the threshold error correction model on milk and cheese. Bor et al (2014) applied an asymmetric error correction model to monthly price data and their results suggest that there is a positive price asymmetry in the farm-retail price transmission in the Turkish milk market.…”
Section: Introductionmentioning
confidence: 99%
“…Producer and consumer prices therefore depend mainly on the two types of price transmission: horizontal and vertical. Price transmission at various stages of vertical chain has received a lot of attention in the literature (Capps and Sherwell, 2007;Fernández-Amador et al, 2010;Stewart and Don, 2011;Bakucs et al, 2012;Bonnet et al, 2015;Zeng and Gould, 2016 and others). These changes have been determined by the speed, magnitude and the nature of the adjustments, which respond to market shocks at the different levels of the chain (Vavra et al, 2005).…”
Section: Introductionmentioning
confidence: 99%